PENGARUH KEADILAN KOMPENSASI TERHADAP KEPUASAN KERJA PERAWAT DI RSUD SULTAN IMANUDDIN PANGKALAN BUN KALIMANTAN TENGAH - Eny Lestari; Heru Kurnianto Tjahjono (Universitas Muhammadiyah Yogyakarta, 2013)
Nurse’s working satisfaction can push nurse’s productivity and performance. Working satisfaction can affect performance and increasing working motivation. Working satisfaction namely can be accomplished by compensation fairness. Dissatisfaction on compensation will impact on decreasing work achievement. This research aim is to know effect of compensation fairness on nurse’s working satisfaction at Region General Hospital of Sultan Imanuddin Pangkalan Bun. This research is quantitative research using cross sectional approach. Research population is nurse that work at Region General Hospital of Sultan Imanuddin Pangkalan Bun. Sampling technique in this research is population samplings with sample number are 152 people. Data collection uses questionnaire. Data analysis uses double regression analysis. Distributive fairness significantly has positive effect on nurse’s satisfaction. Procedural satisfaction do not significantly affect on nurse’s working satisfaction. Interpersonal fairness significantly has positive effect on nurse’s working satisfaction. Compensation fairness significantly affect on nurse’s satisfaction at Region General Hospital of Sultan Imanuddin Pangkalan Bun.